Antibacterial Activity of Lactic Acid Bacteria Isolates Mountain Rice Wash Water (Mayas Rice) Against Propionibacterium acnes - M. Arifuddin; Rezti Amanda; Arfiani Arifin; Arfina Sukmawati Arifin; Iswahyudi Iswahyudi; Erwin Samsul; Riki Riki; Hifdzur Rashif Rija'i; Baso Didik Hikmawan; Arsyik Ibrahim; Laode Rijai (Journal of Pharmaceuticals and Natural Sciences, 2026)
This study aims to explore the antibacterial activity potential of fermented dragon fruit peel juice (Hylocereus polyrhizus) fermented using Lactic Acid Bacteria (LAB) isolated from rice washing water (Beras Mayas). The process begins with the preparation of dragon fruit peel samples, which are washed, peeled, and mashed to obtain the juice. The juice is pasteurized and inoculated with a 5% LAB starter, with the addition of a 10% sugar solution before being incubated for 3, 7, 12, and 17 days at 37ºC. pH measurements were taken during fermentation, showing a significant decrease in pH, reaching the lowest value of 3.76 on day 17. The antibacterial activity was measured using the well-diffusion method with the fermented juice at a concentration of 100%, showing a very strong inhibition zone (>20 mm) against Propionibacterium acnes on day 7. The results indicate that the pH changes during fermentation are closely related to the antibacterial activity